Вы находитесь на странице: 1из 10

3.

3.1.
n-

F x, y , y , , y (n 1) , y (n ) = 0 ,
(3.1)
x , y ,

F G R n + 2

(n 1)

y (n ) .

(3.1) I = (a, b )
y = (x ) , :
1. (x ) C n (a, b ) ;

2. x, , , , (n 1) , (n ) G x (a, b ) ;

3. F x, , , ,

(n 1)

(n )

) = 0 x (a, b) .

, , (3.1) : x0 , y 0 , y 1 , , y n , x 0 (a, b ) F ( x, y 0 , y1 , , y n ) = 0 .
y (x ) (3.1),
y (x 0 ) = y 0 , y (x 0 ) = y 1 , , y (n ) (x 0 ) = y n .
(3.2)
. , y = y (x )
x 0 .
(3.1) ,
x, y n C1 , C 2 , , C n
( x, y, C1 , C 2 , , C n ) = 0 .
(3.3)
37

C1 , C 2 , , C n
,
F x, y, y , , y (n 1) , y (n ) , n

y (x 0 ) = y 0 , y (x 0 ) = y 1 , , y (n 1) ( x 0 ) = y n 1 .

(3.4)

3.2. ,
3.2.1. .
3.2.1.1. ,
x .
3.2.1.2. , y, .. F x, y (k ) , y (k +1) , , y (n ) = 0 , -

, z = y (k ) ,
y ,
.
3.2.1.3.
x, .. F y, y , y , , y (n ) = 0 ,
, y,
p( y ) = y .
d ( y ) dp ( y ) dp dy
=
=

= p ( y ) p( y ) .
y =
dx
dx
dy dx
.
y = y 0 = const ,

:
F ( y , 0, 0, , 0) = 0 .

3.2.2.
.
3.2.2.1. y
y, .. y y , y (k ) y (k ) , 0 , k = 1, 2, , n ,
38

,
z (x ) y = yz .

y = ( y ) = ( yz ) = y z + y z =

= yz z + y z = y z + z 2 .
. y = 0 .
3.2.2.2. , .. s,
x x , y s y ,
y s 1 y , y s 2 y , , y (k ) s k y (k ) ,
0 , k = 1, 2, , n .
, ,
s, ,
. s
,
.
s , x > 0 t z (t )

x = e t , y = ze st .
. x < 0 x = e t .
, t.
, , 3.2.1.3.
.

.

39

3.3. ,
3.1. (8-24).
2
2 yy ln y = ( y ) (1 + 2 ln y ) , y (0 ) = e, y (0) = e .
1 x ,
y = p( y ) , y xx = p y y x = pp .


2 ypp ln y = p 2 (1 + 2 ln y ) .
1) p = 0 y = 0 y = const - ;
2) p 0 2 yp ln y = p(1 + 2 ln y )
.
dp (1 + 2 ln y )
dp 2
1
2
=
dy , 2
= +
dy .
p
y ln y
p y y ln y
2 ln p = 2 ln y + ln ln y + ln C 0

C 0 > 0 ),

..,

p 2 = Cy 2 ln y ( , .. ) ;
) p = 0).
y (0) = y (0) = e . , e 2 = Ce 2 ln e C = 1 ,
dy
= p = y ln y :
dx
dy
= dx ( - ).
y ln y

d ln y
ln y

= x + C 2 ln y = x + C .

y (0) = e , C = 2 .

40

,
: y = e

x
+1
2

.n

3.2. (7-01)

2 y 2 y sin x 2 y 2 y cos x + ( y ) 2 y ( y ) sin x = 0 ,


3



y = 1, y = 1 .
2
2
d , y , y , y , y = yz ,

y = y z + yz = yz z + yz = y z 2 + z .
:
3
2
2 y 2 y z 2 + z sin x 2 y 2 yz cos x + ( yz ) 2 y ( yz ) sin x = 0 .
1. y = 0 ;
2. y 0

2 z 2 + z sin x 2 z cos x + z 3 2 z 2 sin x = 0


2 z sin x 2 z cos x = z 3 .
1
2
p = 2 , p = 3 z .
z
z
2 z sin x 2 z cos x

+
=1

z3
z3
p sin x + 2 p cos x = 1 p, .
1) :

p sin x + 2 p cos x = 0 .
dp
2 cos xdx
p0
=
ln p = 2 ln sin x + ln C 0
p
sin x
C
p=
.
sin 2 x

41

2) C = C (x ) , p =

C (x )
sin 2 x


C
2C cos x
C
sin x
sin x + 2
cos x = 1 C = sin x ,
2
3
sin x
sin x
sin 2 x
.. dC = sin xdx C (x ) = cos x + C1
3) C ( x ) ,
cos x + C1

1
sin 2 x
=
.
p cos x + C1
sin 2 x
C1 p=

, .. z 2 =



y = 1, y = 1 . ,
2
2

y
1


2 1
z =
=
= 1 z 2 = 1 =
C1 = 1
C1
1
2
2
y
2

y
sin x

=
, .. y y x =
,
y
2
1 cos x
y
sin x
:
=
y
1 cos x
dy
sin dx

,
..
=

y
1 cos x

ln y = 2 1 cos x + C 2 .

y = 1 ,
2
ln 1 = 2 1 0 + C 2 , C 2 = 2 ln y = 2 2 1 cos x , ,
.. y > 0 , , -

: y = exp 2 2 1 cos x . o
42

3.4.
:
3
2
57. (7-01) 2 y 2 y sin x 2 y 2 y cos x + ( y ) 2 y ( y ) sin x = 0 ,


y = 1 , y = 1 .
2
2

58. (7-02) 4 yy + 4 y 2 1 ( y )6 + ( y )2 = 0 , y (2 ) = 1 , y (2 ) = 1 .
59. (7-03) 2 y y cos x + 2 y 2 y sin x + ( y )3 2 y ( y )2 cos x = 0 ,
2

3


y = 1 , y =
.
2
6
6

1
2

60. (7-04) 4 yy + y 2 9 ( y )6 + ( y )2 = 0 , y (0) = 1 , y (0 ) = .


61. (6-11) yy + 2 x( y )2 = xyy , y (1) = 1, y (1) = 1 .
62. (6-12) 3 yy 3( y )2 = 4 y ( y )5 , y (0 ) = 1, y (0) = 1 .
63. (6-13) yy xyy + x( y )2 = 2 x( y )2 ln x , y (1) = 1, y (1) = 2 .
64. (6-14) y ( y 1)2 + ( y )2 ( y 1) = ( y )3 , y (0 ) = 2, y (0 ) = 2 .

65. (8-21) 2 x y 2 y + ( y )3 = y y 2 + 2 xy( y )2 , y (1) = y (1) = 1 .


66. (8-22) y ( y 1) + y ( y 1)2 = ( y )2 , y (0 ) = 2, y (0 ) = 2 .
67. (8-23) xyy = yy + x( y )2 + 4 x 5 y 2 , y (1) = 1, y (1) = 1 .
68. (8-24) 2 yy ln y = ( y )2 (1 + 2 ln y ) , y (0) = e, y (0) = e .

69. (8-31) yy = ( y )2 y 2 y + 1 , y (0) = 1, y (0) = 3 .


70. (8-32) y y 2 x 2 xy 2 y x 2 ( y )2 y
y (2 ) = 1, y (2) = 2e .

ex
( y )3 = 0 ,
2

71. (8-33) y y ( y )3 ctg y + cos 2 y sin 4 y = 0 , y (0) =

, y (0) =

72. (8-34) yy yy ( y )2 e x + 1 = 0 , y (1) = sh 1, y (1) = 1 .


1
e

73. (5-41) x 2 yy 2 x 2 ( y )2 + xyy = 0 , y (e ) = 1, y (e ) = .


74. (5-42) xyy 2 x( y )2 + yy = 0 , y (1) = y (1) = 1 .
43

1
.
2

75. (5-43) y 2 y y ( y )2 y 3 = 0 , y (0 ) = 1, y (0) = 1 .


76. (5-44) xyy + x( y )2 yy = 0 , y (1) = 4, y (1) = 1 .
77. (5-51) 3 y 2 y y + 2 y ( y )3 = 4 y 3 , y (1) = 1, y (1) = 1 .
78. (5-52) 4 yy + ( y )2 + y ( y )4 = 0 , y (1) = 1, y (1) = 1 .
79. (5-53) 2( y + 1)y + ( y )2 = 2( y + 1) , y (2 ) = 0, y (2 ) = 1 .
80. (5-54) yy + 3( y )2 = y 2 ( y )3 , y (4) = 2, y (4) =

1
.
4

81. (5-61) xyy + 2 x 3 ( y )2 yy = 0 , y (1) = y (1) = 1 .

2
.
82. (5-62) y + ( y )2 tg y ( y )4 sin 2 y = 0 , y (0) = , y (0) =
6

83. (5-63) xyy + x ( y ) + 3 yy = 0 , y (1) = 1, y (1) = 2 .


4

84. (5-64) y ( y )2 th y + ( y )4 sh 2 y = 0 , y (0) = 0, y (0) = 1 .

3.6.

57. y = exp 2 2 1 cos x .

1
(7 3x )2 3 + 1 .
2

58. y =

59. y = exp 2 2 sin x .

3
2

23

60. y = 8 x

3.

61. . y =

x +1
34

4
x .
3

63. y = 1 2 ln x .

62. y = 1

64. y = 1 + e 2 x .
65. y = e 2
66. y =

x 2

2e x
2e x 1

.
44

67. y

x 6 1
=e 6

68. y

x
+1
= e 2

.
2

69. y = 1 9 x .

70. y = exp (4 2 x )e 2 .

( )

71. y = arctg e x .
e x + 1 (e 1)2

.
x

e 1 2e
1
73. y =
.
ln x
1
74. y =
.
1 ln x

72. y =

75. y = e

1
x+ x2
2

76. y = 2 x 2 + 3 .
3

x4
.
3

77. y =

5 3x 3
78. y =
.
2
2

x4
1.
2

79. y =

80. y = 3 3 x 4 .
81. y =

2x 2

x2 +1

1
82. y = arcsin x .

45

83.

(2 x
y=

1
x2

23

84. y = ln x + x 2 + 1 x = sh y .

46